Hybrid Organic-Inorganic Materials and Interfaces With Mixed Ionic-Electronic Transport Properties: Advances in Experimental and Theoretical Approaches - Romero, Mariano; Mombrú, Dominique; Pignanelli, Fernando; Faccio, Ricardo; Mombrú, Alvaro W. (Frontiers in Chemistry, 2022)
The main goal of this mini-review is to provide an updated state-of-the-art of the hybrid organic-inorganic materials focusing mainly on interface phenomena involving ionic and electronic transport properties. First, we review the most relevant preparation techniques and the structural features of hybrid organic-inorganic materials prepared by solution-phase reaction of inorganic/organic precursor into organic/inorganic hosts and vapor-phase infiltration of the inorganic precursor into organic hosts and molecular layer deposition of organic precursor onto the inorganic surface. Particular emphasis is given to the advances in joint experimental and theoretical studies discussing diverse types of computational simulations for hybrid-organic materials and interfaces. We make a specific revision on the separately ionic, and electronic transport properties of these hybrid organic-inorganic materials focusing mostly on interface phenomena. Finally, we deepen into mixed ionic-electronic transport properties and provide our concluding remarks and give some perspectives about this growing field of research.